Evaluating the efficacy of eco-religious communication in fostering pro-environmental behavior - Ramadaniar, Putri; Kuswanti, Ana; Ayuningtyas, Fitria; Abdul Muqsith, Munadhil (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
Islamic boarding schools (pesantren) in Indonesia, as Islamic educational institutions experiencing significant growth, are now facing complex external challenges, particularly the climate crisis. A limited technical understanding of how ecological values in Islamic teachings can be translated into practice also remains a barrier. This study aims to analyze the role of progressive pesantren in building awareness and collective action to address the climate crisis through religious communication strategies. Using a quantitative approach, this study applies the Theory of Planned Behavior (TPB) to explain how attitudinal factors, subjective norms, and perceived behavioral control can shape pro-environmental intentions within the pesantren community. This study tests the classical communication theory of TPB. The study population comprises all components of the pesantren, including students, kiyais, teachers, and stakeholders. More specifically, the population is the pesantren ecosystem in West Java that has implemented environmentally sound practices. The sampling technique employed was simple random sampling, with a population of 391. The sample size was calculated using the Slovin formula, resulting in 198 respondents. Data were collected through a questionnaire distributed directly to the respondents. The data analysis techniques included descriptive analysis and SmartPLS 3 operationalization. The result is an eco-religious amplification model, which empirically shows that religious communication requires mediation through an eco-religious approach, local wisdom, and cognitive reinforcement to transform religious messages into genuine concern about the climate crisis.